Relationship Between Advanced Maternal Age and Timing of First Developmental Evaluation in Children with Autism. Issue 8 (October 2018) - Rubenstein, Eric; Durkin, Maureen S.; Harrington, Rebecca A.; Kirby, Russell S.; Schieve, Laura A.; Daniels, Julie
ABSTRACT: Objective: Mothers of advanced maternal age (AMA) at childbirth (age ≥35 years) may have different perceptions of autism spectrum disorder (ASD) risk, independent of sociodemographic factors, that may affect ASD identification. We aimed to estimate associations between AMA and both age of a child's first evaluation noting developmental concerns and time from first evaluation to first ASD diagnosis. Methods: We used data for 8-year-olds identified with ASD in the 2008 to 2012 Autism and Developmental Disabilities Monitoring Network. We estimated differences in age at first evaluation noting developmental concerns and time to first ASD diagnosis by AMA using quantile and Cox regression. Results: Of 10, 358 children with ASD, 19.7% had mothers of AMA. AMA was associated with higher educational attainment and previous live births compared with younger mothers. In unadjusted analyses, AMA was associated with earlier first evaluation noting developmental concerns (median 37 vs 40 mo) and patterns in time to first evaluation (hazard ratio: 1.12, 95% confidence interval: 1.06–1.18). Associations between AMA and evaluation timing diminished and were no longer significant after adjustment for socioeconomic and demographic characteristics. Children's intellectual disability did not modify associations between AMA and timing of evaluations. Conclusion: Advanced maternal age is a sociodemographic factor associated with younger age of first evaluation noting developmental concerns in children with ASD, but AMA was not independently associated likely, because it is a consequence or cofactor of maternal education and other sociodemographic characteristics. AMA may be a demographic factor to consider when aiming to screen and evaluate children at risk for ASD.